An investigation of certain aspects of pyruvate metabolism in man by indirect and direct tolerance tests - Lange, Leo Stanley (Department of Medicine, 2020)
The purpose of this project has been to test the postulate that high blood levels of pyruvate encountered in certain conditions such as steroid excess, diabetes mellitus under certain circumstances, and thiamine deficiency, are due to defective removal of pyruvate rather than excessive production. Specific methods of assay and direct studies of pyruvate tolerance were used. Intermediary carbohydrate metabolism was studied in a total of 109 subjects. The history of thiamine deficiency and of the concept of ensymes is outlined and the literature on pyruvate estimation and study in various clinical conditions is reviewed. Direct tests of pyruvate tolerance are discussed and the biochemistry if glucose breakdown is described. the history of analytical methodology for pyruvate is recounted.